Sotatercept with long-term extension for the treatment of anaemia in patients with lower-risk myelodysplastic syndromes: a phase 2, dose-ranging trial. Issue 2 (February 2018) - Komrokji, Rami; Garcia-Manero, Guillermo; Ades, Lionel; Prebet, Thomas; Steensma, David P; Jurcic, Joseph G; Sekeres, Mikkael A; Berdeja, Jesus; Savona, Michael R; Beyne-Rauzy, Odile; Stamatoullas, Aspasia; DeZern, Amy E; et al.
Summary: Background: Myelodysplastic syndromes are characterised by ineffective erythropoiesis leading to anaemia. Sotatercept (ACE-011) is a novel activin receptor type IIA fusion protein that acts as a ligand trap to neutralise negative regulators of late-stage erythropoiesis. The aim of the study was to establish a safe and effective dose of sotatercept for the treatment of anaemia in patients with lower-risk myelodysplastic syndromes. Methods: This open-label, multicentre, dose-ranging, phase 2 trial took place at 11 treatment centres in the USA and France. Eligible patients were aged 18 years or older, had International Prognostic Scoring System-defined low-risk or intermediate-1-risk myelodysplastic syndromes, had anaemia requiring red blood cell (RBC) transfusions, and were ineligible for, or refractory to, erythropoiesis-stimulating agents (ESAs). Patients were not eligible if they had chromosome 5q deletion myelodysplastic syndromes without documented failure of lenalidomide. Patients were randomly assigned to receive either 0·1 or 0·3 mg/kg sotatercept subcutaneously, using a permuted-block method with stratification for serum erythropoietin concentration and transfusion burden. Patients were assigned to 0·5, 1·0, and 2·0 mg/kg groups in a non-randomised fashion. The primary efficacy endpoint was the proportion of patients who achieved haematological improvement–erythroid (HI-E), according to International Working Group 2006 criteria. Efficacy and safety analyses were done in the intention-to-treat population. This trial is registered atClinicalTrials.gov, numberNCT01736683 and at EU Clinical Trials Register, number 2012–002601–22, and is ongoing. Findings: Between Dec 5, 2012, and July 22, 2015, 74 patients were enrolled into the study (seven to receive 0·1 mg/kg sotatercept, six to 0·3 mg/kg, 21 to 0·5 mg/kg, 35 to 1·0 mg/kg, and five to 2·0 mg/kg). 36 (49%; 95% CI 38–60) of 74 patients achieved HI-E; 29 (47%; 95% CI 35–59) of 62 patients with a high transfusion burden achieved HI-E (RBC-transfusion reduction from baseline of 4 or more units for at least 56 days), and seven (58%; 95% CI 32–81) of 12 patients with a low transfusion burden achieved HI-E (haemoglobin increase of 1·5 g/dL or more sustained for at least 56 days in the absence of transfusions). The most commonly reported adverse events were fatigue in 19 (26%) of 74 patients and peripheral oedema in 18 (24%) of 74 patients. Grade 3–4 treatment-emergent adverse events (TEAEs) were reported in 25 (34%) of 74 patients; four (5%) patients had grade 3–4 TEAEs that were considered to be treatment related. The most common grade 3–4 TEAEs were lipase increase and anaemia, which each occurred in three (4%) of 74 patients. 17 (23%) of 74 patients had at least one serious TEAE, and one patient died from a treatment-emergent subdural haematoma due to a fall. Interpretation: Sotatercept, a novel activin-receptor fusion protein, was well tolerated and effective for the treatment of anaemia in patients with lower-risk myelodysplastic syndromes in whom previous ESA treatment had failed. Treatment with sotatercept could be beneficial for these patients who have few available treatment options. Funding: Celgene Corporation.